Nutritional value, physico-chemical properties and acceptability of rice (Oryza sativa L.) and corn (Zea Mays L.) composites. - Nagares, N. D. L. (Compendium of Human Ecology Researches in the Philippines, 2003)
IR 72 rice variety (high-amylose type) was combined with IPB Var. 6, a Quality Protein Maize (QPM) white corn, obtaining a total of nine different rice-corn composites (rice and corn combination). QPM contains nearly twice as much usable protein that is specifically rich in lysine and tryptophan, the two limiting essential amino acids in rice. Addition of QPM white corn grits to IR 72 rice variety increased the amount of protein, lysine, tryptophan, fat, ash, starch, amylose and total fiber content of the rice-corn composites. Gel consistency and hardness were relatively higher in samples having more corn. Both IR 72 rice variety and QPM white corn have the same gelatinization temperature below 70°C. Generally, based on a 7-point Hedonic rating scale for evaluation, all the rice-corn composites were considered acceptable in terms of color, odor, flavour, cohesiveness, and texture. There was a significant difference in each sensory attribute except cohesiveness. The sensory evaluation showed that the 70:30 (rice:corn) ratio had the highest preference score in terms of flavour and general acceptability. The study showed that combining IR 72 rice variety and QPM white corn grits at a 70:30 ratio can be utilized as a staple food owing to its improved nutritional and sensory qualities and thus, can be used to ameliorate food insecurity in the Filipino families and homes.